2018
DOI: 10.1016/j.apenergy.2017.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Community energy storage: A smart choice for the smart grid?

Abstract: Energy storage can help integrate local renewable generation, however the best deployment level for storage remains an open question. Using a data-driven approach, this paper simulates 15-minute electricity consumption for households and groups them into local communities of neighbors using real locations and the road network in Cambridge, MA. We then simulate PV for these households and use this framework to study battery economics in a high PV adoption, high electricity cost scenario, in order to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(91 citation statements)
references
References 41 publications
1
71
0
Order By: Relevance
“…The present study optimizes prosumer PV battery investments and operation so as to minimize the cost for the prosumer. Analyzing a case with a fixed share of solar PV that is already installed (instead of joint optimization of PV and battery capacities as in our study), Barbour et al have shown that less storage capacity is required for a prosumer community energy storage system than for individual household storage systems, which is in line with the results of our study. In this work the incentive to avoid taxes and fees on bought electricity through local self‐consumption of electricity has a greater impact on the optimization and operation of PV battery investments than do the peaks and lows in the hourly electricity price.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study optimizes prosumer PV battery investments and operation so as to minimize the cost for the prosumer. Analyzing a case with a fixed share of solar PV that is already installed (instead of joint optimization of PV and battery capacities as in our study), Barbour et al have shown that less storage capacity is required for a prosumer community energy storage system than for individual household storage systems, which is in line with the results of our study. In this work the incentive to avoid taxes and fees on bought electricity through local self‐consumption of electricity has a greater impact on the optimization and operation of PV battery investments than do the peaks and lows in the hourly electricity price.…”
Section: Discussionsupporting
confidence: 89%
“…Research has been conducted on the topics of energy autarky and self‐consumption on different scales, from individual buildings to neighborhoods and districts, as well as on the clustering of prosumers to optimize power grid operation and reduce costs . Community energy storage has been investigated in terms of economic benefits and possibilities to integrate renewable energy sources and demand‐side management . There have also been studies on the interactions that occur on local markets, the different energy carriers in a local energy community or energy hub, and the effects of different load curves on neighborhood clusters …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a common way to describe renewable energy communities is as 'those projects where communities (of place or interest) exhibit a high degree of ownership and control in renewable energy production as well as benefiting collectively from the outcomes' [23]. Such communities for example consist of local energy cooperatives that develop collective energy practices [24], such as collectively generating solar energy for local use.…”
Section: New Collective Materials Practicesmentioning
confidence: 99%
“…The effects of different factors are analyzed for a deeper understanding. More specifically, using the historical data of the Pecan Street smart community 8 and the corresponding weather information, a BPNN-based prediction has been conducted. The performances under different time resolutions, hourly, daily, weekly, and monthly, are investigated.…”
Section: Introductionmentioning
confidence: 99%